The impacts of a GO-game (Chinese chess) intervention on Alzheimer disease in a Northeast Chinese population - Lin, Qiao; Cao, Yunpeng; Gao, Jie (Frontiers in Aging Neuroscience, 2015)
A GO game can enhance mental health, but its effects on Alzheimer Disease (AD) remains unknown. To address the issue, 147 AD patients were randomly assigned into control (without GO-game intervention), Short-time GO-Game Intervention (SGGI, one hour daily) and Long-time GO-game Intervention (LGGI, two hours daily) groups. After 6-month follow-up, the game reduced the mean score of Montgomery-Asberg Depression Rating Scales (MADRS) of 4.72(95% CI, 0.69 to 9.12) and Hospital Anxiety and Depression Scale (HADS) of 1.75 (95% CI, 0.17 to 3.68), and increased the mean score of Global Assessment of Functioning (GAF) of 4.95 (95% CI, -1.37 to 9.18) and RAND-36 of 4.61 (95% CI, -2.75 to 11.32) (P < 0.05 via controls). A GO-game intervention improved 9 of 11 items of KICA-dep (Kimberley Indigenous Cognitive Assessment of Depression). Meanwhile, serum levels of brain derived neurotrophic factor (BDNF) were higher in SGGI and LGGI groups (24.02 ± 7.16 and 28.88 ± 4.12 ng/ml respectively, P = 0.051) than those in controls (17.28 ± 7.75 ng/ml) (P < 0.001). The serum levels of BDNF showed a negative relation with MADRS and a positive relation with RAND-36 (P < 0.01). A GO-game intervention ameliorates AD manifestations by up-regulating BDNF levels.